QZSS L5 Bandwidth Frequency Filter Design for QZSS Receiver - Julongkorn Pattameak; Narumon Onanong; Teerachet Makpradab; Surachet Chinnapark; Prasert Kenpankho (Universitas Pendidikan Indonesia (UPI), 2022)
The purpose of this study was to design QZSS L5 Bandwidth Frequency Filter for QZSS Receiver. We presented the configuration of the Butterworth bandpass filter by using PSpice as the tool for the simulation. Bandpass filter frequency of the QZSS L5 with bandwidth is designed in 25 MHz using the Butterworth filter which is presented in this article. These designed circuits are composed of the 3rd order. Moreover, the combination between low pass filter and high pass filter is performed as a bandpass filter. In conclusion, this designed filter on the frequency of QZSS L5 is to be useful by using the Butterworth bandpass filter.